2015
DOI: 10.1073/pnas.1510854112
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular communication in Arabidopsis thaliana pollen discovered via AHG3 transcript movement from the vegetative cell to sperm

Abstract: An Arabidopsis pollen grain (male gametophyte) consists of three cells: the vegetative cell, which forms the pollen tube, and two sperm cells enclosed within the vegetative cell. It is still unclear if there is intercellular communication between the vegetative cell and the sperm cells. Here we show that ABA-hypersensitive germination3 (AHG3), encoding a protein phosphatase, is specifically transcribed in the vegetative cell but predominantly translated in sperm cells. We used a series of deletion constructs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The authors provided evidence that AHG3 transcripts move from the vegetative cell to sperm cells, and that transport requires sequences in both the 5′ UTR and coding region. The mechanisms involved and the extent of communication via this route are not yet clear, but these results document an additional role for the vegetative cell in shaping the sperm cell transcriptome (Jiang et al, 2015). He et al 2015).…”
Section: Communication Between Non-germ and Germ Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors provided evidence that AHG3 transcripts move from the vegetative cell to sperm cells, and that transport requires sequences in both the 5′ UTR and coding region. The mechanisms involved and the extent of communication via this route are not yet clear, but these results document an additional role for the vegetative cell in shaping the sperm cell transcriptome (Jiang et al, 2015). He et al 2015).…”
Section: Communication Between Non-germ and Germ Cellsmentioning
confidence: 97%
“…While studying the expression of the sperm cell-enriched ABA-related protein phosphatase gene ABA-HYPERSENSITIVE GERMINATION3 (AHG3), Jiang and coworkers (2015) unexpectedly found that the AHG3 promoter was transcriptionally active in the vegetative cell, whereas a translational fusion protein was localized to sperm (Jiang et al, 2015). The authors provided evidence that AHG3 transcripts move from the vegetative cell to sperm cells, and that transport requires sequences in both the 5′ UTR and coding region.…”
Section: Communication Between Non-germ and Germ Cellsmentioning
confidence: 99%
“…To generate atx4 atx5 double mutants, atx4-1 was crossed with atx5-1 mutants, and double mutants were screened using ATX4-1LP/RP and ATX5-1LP/RP PCR primers. To generate atx4-1 ahg3-1 and atx5-1 ahg3-1 double mutants and the atx4-1 atx5-1 ahg3-1 triple mutant, atx4-1, atx5-1 and atx4-1 atx5-1 mutants, respectively, were crossed with the ahg3-1 mutant (Nishimura et al, 2004;Jiang et al, 2015), and mutants were screened using primers ATX4-1LP/RP, ATX5-1LP/RP and AHG3-LP/RP, respectively. All PCR primers used for genotyping are listed in Supporting Information Table S1.…”
Section: Plant Growth Conditions and Genotypingmentioning
confidence: 99%
“…Thus, we reasoned that the hypersensitive phenotypes of the atx4 and atx5 mutants in response to ABA might be attributable to a reduction of AHG3 transcript levels in the mutants. To test this idea, we crossed the ahg3-1 mutant (Nishimura et al, 2004;Yoshida et al, 2006;Jiang et al, 2015) with the atx4-1, atx5-1 or atx4-1 atx5-1 mutant line and generated atx4-1 ahg3-1, atx5-1 ahg3-1, and atx4-1 atx5-1 ahg3-1 mutant lines, respectively, and further tested the ABA sensitivity in terms of seed germination. As shown in Fig.…”
Section: Atx4 and Atx5 Play Partially Redundant Roles In Plant Growthmentioning
confidence: 99%
“…This physical connection allows it to travel as a unit through the growing pollen tube to the female gametophyte where fertilization of the egg and the central cell generates the embryo and the endosperm, respectively (McCue et al 2011 ; Ge et al 2011 ). Additionally, molecular data suggest that MGU linkage is essential for communication between the VC and SCs (Tian et al 1998 ; Slotkin et al 2009 ; Hamamura et al 2011 ; Grant-Downton et al 2013 ; Jiang et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%